Hyperoodon planifrons Flower 1882 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
5. Southern Bottlenose Whale Hyperoodon planifrons French: Baleine-a-bec australe / German: Sidlicher Entenwal / Spanish: Zifio calderén meridional Other common names: Antarctic Bottlenose, Flatheaded Bottlenosed Whale, Flower’s Bottle-nosed Whale, Pacific Beaked Whale Taxonomy. Hyperoodon planifrons Flower, 1882, “found upon the sea-beach of Lewis Island in the Dampier Archipelago, north-western Australia.” This species is monotypic. Distribution. Subantarctic and Antarctic waters from Antarctica to South Africa, S Australia, N New Zealand, and South America. Its occurrence appears to be relatively continuous within its distribution. Descriptive notes. Total length 650- 750 cm; weight ¢.6000-7500 kg. Unlike the closely related Northern Bottlenose Whale (H. ampullatus), there is no evidence that male Southern Bottlenose Whales are larger than females; however, this may be due to a lack of information because there are few accurate measurements of body length. Body is spindle-shaped, with greatest girth around its mid-point. Flukes are wide in relation to body length, and tailstock is compressed laterally. Dorsal fin is small and set approximately two-thirds of the distance between tip of the beak and end of the tail. Coloration is typically dark brown, dark gray, or black. Unlike many other species of beaked whales, Southern Bottlenose Whales do not seem to accumulate white linear scars from intraspecific aggression. Rostrum and lower jaw form a short but well-defined beak, and there are two grooves on the throat. There appears to be similar sexual dimorphism in shape of the forehead of the Southern Bottlenose Whale to that found in the Northern Bottlenose Whale, with the forehead of males becoming enlarged as they mature, but the Southern Bottlenose Whale does not develop large bony crests on maxillary bones of the skull, which is one of the most notable differences between the two species. Unlike many other species of beaked whales, adult male Southern Bottlenose Whales have no functional teeth and lack tusks ...